Weak Form Efficiency of the Nigerian Stock Market: An Empirical Analysis (1984 – 2009) - Pyemo Afego (International Journal of Economics and Financial Issues, 2012)
This paper examines the weak-form of the efficient markets hypothesis for the Nigerian Stock Exchange (NSE) by testing for random walks in the monthly index returns over the period 1984-2009. The results of the non-parametric runs test show that index returns on the NSE display a predictable component, thus suggesting that traders can earn superior returns by employing trading rules. Statistically significant deviations from randomness are also suggestive of sub-optimal allocation of investment capital within the economy. The findings, in general, contradict the weak-form of the efficient markets hypothesis, and a range of policy strategies for improving the allocative capacity and quality of the information environment of the NSE are discussed.